Study on the Effect of Quasi-Radical Lesion Resection on the Quality of Life of Patients With Advanced Hepatic Alveolar Echinococcosis - A, Jide; Chai, Jinping; Guo, Wenlu; Zhao, Shunyun; Wang, Hao; A, Xiangren; Yang, Jinyu (Frontiers in Surgery, 2022)
Objective: To retrospectively analyze the effects of radical lesion resection and quasi radical lesion resection on the quality of life of patients with advanced hepatic alveolar echinococcosis. Methods: through the existing his system of Qinghai Provincial People's Hospital, 104 patients with hepatic alveolar echinococcosis who underwent surgical treatment in our hospital from January 2012 to December 2017 and completed the quality of life questionnaire were selected as the research objects. The above cases were divided into radical group (n = 51) and quasi radical group (n = 53) according to different surgical methods (degree of radical cure). The quality of life of patients with hydatidosis was measured by interview or telephone follow-up. The preoperative indexes, intraoperative conditions and postoperative recovery of the two groups were observed, such as child puhg grade, operation mode, intraoperative bleeding, severity of surgical complications, incidence of complications, overall survival time and total score of quality of life. Results: there was no significant difference between the two groups in general data such as age, gender, hydatid size, complications, child puhg grade and preoperative liver function（P>0.05）.There were significant differences in intraoperative bleeding, postoperative liver function recovery and Clavien grade of complication severity between the two groups（P<0.05）.There was no significant difference in postoperative overall survival time and quality of life between the two groups（P>0.05）. Conclusion: For patients with advanced hepatic alveolar echinococcosis whose objective cannot be achieved by conventional hepatectomy, quasi-radical resection of the lesion can not only reduce the risk and difficulty of surgery, but also the overall postoperative survival time and quality of life of the patient may be as good as that of radical resection.